Breeding patterns in the pre-desert oniscid isopod Porcellio buddelundi of Matmata (Gabès, Tunisia). Issue 4 (2nd October 2017) - Medini-Bouaziz, Lamia; Naceur Fessi, Amira; Charfi-Cheikhrouha, Faouzia
Abstract: Porcellio buddelundi inhabits arid areas in Tunisia. The reproductive pattern of a population at Oued El Jir, Matmata (Tunisia) was studied from July 2005 to June 2006. Monthly samples were taken during the study period. The overall sex ratio was biased toward females. Males, females, and newborns all had greater body-mass in autumn than in spring and their lowest mean body-mass was in June and July. Ovigerous females greater than 41.1 mg in body-mass, were collected from March through May and from September through October, suggesting seasonal reproduction with two breeding seasons: the longer one in spring (3 months) and another in the fall (2 months). Fecundity, which was positively correlated with the body-mass of females, varied between breeding seasons with a large number in spring and a small number in autumn. Seasonal variation of fecundity could be explained by the growth rate of ovigerous females affecting the fecundity more in spring than in autumn. The onset of breeding, in P. buddelundi, takes place when the day-length exceeds 12 h and the soil moisture decreases.